Childhood Exposure to Religions With High Prevalence of Members Who Discourage Homosexuality Is Associated With Adult HIV Risk Behaviors and HIV Infection in Black Men Who Have Sex With Men. (September 2017) - Nelson, LaRon E.; Wilton, Leo; Zhang, Nanhua; Regan, Rotrease; Thach, Chia T.; Dyer, Typhanye V.; Kushwaha, Sameer; Sanders, Rev. Edwin C.; Ndoye, Omar; Mayer, Kenneth H.
Exposure to childhood religious affiliations where the majority of members discourage homosexuality may have negative psychological impacts for Black men who have sex with men. This study tested the hypothesis that exposures to these environments during childhood were associated with adulthood human immunodeficiency virus (HIV)/sexually transmitted infection (STI) behavioral risk and HIV infection, because these exposures influenced HIV/STI risk by undermining race/sexual identity congruence and increasing internalized homophobia and interpersonal anxiety. Structural equation modeling as well as logistic and Poisson regressions were performed using baseline data from HIV Prevention Trials Network 061 ( N = 1, 553). Childhood religion affiliations that were more discouraging of homosexuality were associated with increased likelihood of HIV infection; however, the association was no longer significant after adjusting for age, income, and education. Having a childhood religion affiliation with high prevalence of beliefs discouraging homosexuality was associated with increased numbers of sexual partners (adjusted odds ratio = 4.31; 95% confidence interval [3.76, 4.94], p < .01). The hypothesized path model was largely supported and accounted for 37% of the variance in HIV infection; however, interpersonal anxiety was not associated with HIV/STI risk behaviors. Structural interventions are needed that focus on developing affirming theologies in religious institutions with Black men who have sex with men congregants.